Deep centers in InGaAs/InP layers grown by molecular beam epitaxy - Kowalczyk, Anna E.; Ornoch, Leszek; Muszalski, Jan; Kaniewski, Janusz; Bąk-Misiuk, Jadwiga (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The deep level transient spectroscopy (DLTS) method was applied to study deep centers in lattice mismatched InGaAs/InP layers grown by molecular beam epitaxy. The composition and the strain state of the layers were determined using X-ray diffraction technique. Electron trap with thermal activation energy EC – (0.06 ± 0.03) eV and electron capture cross-section se = 9.0×10–19 cm–2 have been detected in In0.524Ga0.476As layers being under tensile strain. Additionally two other centers with thermal activation energy EC – (0.10 ± 0.02) eV, and EC – (0.48 ± 0.02) eV have been revealed in In0.533Ga0.467As/InP layers subjected to small compressive strain. The electron capture cross-sections of these traps, determined from emission processes, are equal to se = 6.7×10–18 cm–2 and se = 1.6×10–14 cm–2, respectively. Due to temperature stresses, defect states in the In0.533Ga0.467As/InP layers are modified and the center EC – (0.06 ± 0.03) eV is created. This center is identical to that observed in In0.524Ga0.476As layers, as it has been confirmed by electron capture process measurements. The EC – (0.06 ± 0.03) eV state exhibits a point-like defect character.
Optica Applicata, Vol. 35, 2005, nr 3, s. 457-463
Keywords: optyka; InGaAs; deep centers; deep level transient spectroscopy (DLTS)